Export Taxes and Trade Pattern: Case from the Indonesian Mineral Industry - Made Putra Adhi Laksana (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
The Indonesian government adopted mineral export taxes by imposing a high tariff on raw materials while waiving tariffs on processed products. Tariffs decreased following the progress of refinery plant construction. Based on the fixed effects panel regression at the commodity-country-pair level, this study finds that the export taxes system negatively reduces raw material export while increasing processed mineral export. Tariff stratification on mineral commodities distorts trade patterns, affecting business orientation in upstream and downstream sectors. Furthermore, tier tariff significantly elevates the export quantity of downstream products compared to flat export taxes, directly proportional to export value. Export contraction of raw materials resulted from tier tariff slightly lower than the flat type but with a higher exports performance of processed products. The shifting phenomena to the value-added industry indicate an effort for export taxes evasion. This finding is reinforced by the massive investment inflow in the mineral processing sector. Meanwhile, the exporter manufacturing industry positively correlates with the export performance of processed products and a negative direction with raw material, which aligns with the main finding.